2018
DOI: 10.1371/journal.pone.0207746
|View full text |Cite
|
Sign up to set email alerts
|

Effect of behavioral inhibition system and childhood emotional neglect on serotonergic activity, negative affect, and rejection sensitivity in non-clinical adults

Abstract: IntroductionBehavioral inhibition system (BIS) has a strong genetic basis, and emotional neglect (EN) in childhood is one of many environmental experiences that can affect individuals. This study aimed to examine the effects and interaction between BIS and EN on central serotonergic activity and other negative affect and cognition.MethodsA total of 153 non-clinical volunteers (54 men and 99 women; average age, 27.72 years, standard deviation = 6.40) were included in the analyses. The Behavioral Inhibition Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 74 publications
0
6
0
1
Order By: Relevance
“…Their correlation analysis showed that positive mood was positively correlated with flexibility. Moreover, individuals with CEN, even adults, still have more negative affectivity (Jin et al, 2018 ; Schimmenti et al, 2015 ). For example, Schimmenti et al ( 2015 ) examined the relationships between CEN, current psychiatric symptoms, and negative affectivity in community adults.…”
Section: Discussionmentioning
confidence: 99%
“…Their correlation analysis showed that positive mood was positively correlated with flexibility. Moreover, individuals with CEN, even adults, still have more negative affectivity (Jin et al, 2018 ; Schimmenti et al, 2015 ). For example, Schimmenti et al ( 2015 ) examined the relationships between CEN, current psychiatric symptoms, and negative affectivity in community adults.…”
Section: Discussionmentioning
confidence: 99%
“…For the purposes of this paper, emotional neglect is the result of a caregiver's inability to provide healthy emotional stimulation due to organic issues with the caregiver, such as struggling with unresolved trauma creating low maternal/paternal warmth, substance use disorder, mental health issues, developmental disability, and/or mental health issues. Poverty can also create considerable environmental issues that result in unintentional emotional neglect (Jin et al, 2018). Psychological abuse is purposeful maltreatment that is executed with the intention to harm and/or punish a child.…”
Section: Discussionmentioning
confidence: 99%
“…A Neuroscan Syn-Amps amplifier (Compumedics USA, El Paso, TX, USA) with 64 Ag-AgCl electrodes on a Quik-Cap was used to record the EEG in an extended 10-20 placement scheme. The specific protocol has been described elsewhere [26,27].…”
Section: Qeeg and Proceduresmentioning
confidence: 99%